Clustering for competitiveness in agriculture. Pre-feasibility studies for selected agribusiness clusters in the Caribbean - Glean, Allister (IICA, 2021)
This document is intended to inform and guide future pre-feasibility efforts for selected agribusiness groups in the Caribbean. It is offered as support to the dialogue towards the definition of strategies for the development of competitive companies, firms, industries and value chains in agriculture in CARICOM.